2007
DOI: 10.1016/j.trstmh.2007.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Argemone mexicana decoction for the treatment of uncomplicated falciparum malaria

Abstract: Summary A prospective, dose-escalating, quasi-experimental clinical trial was conducted with a traditional healer using a decoction of Argemone mexicana for the treatment of malaria in Mali. The remedy was prescribed in three regimens: once daily for 3 days (Group A; n = 23); twice daily for 7 days (Group B; n = 40); and four times daily for the first 4 days followed by twice daily for 3 days (Group C; n = 17). Thus, 80 patients were included, of whom 80% were aged <5 years and 25% were aged <1 year. All prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 16 publications
0
60
0
2
Order By: Relevance
“…16 The proportion of patients with parasitaemia at day 28 was 63-76% in the AM group and 21-49% in the ACT group (lower and upper estimates, P < 0.001 with both estimates). Gametocytes were present at day 28 in 13% of the AM group compared with 3% of the ACT group (P = 0.005).…”
Section: Clinical Efficacymentioning
confidence: 87%
See 1 more Smart Citation
“…16 The proportion of patients with parasitaemia at day 28 was 63-76% in the AM group and 21-49% in the ACT group (lower and upper estimates, P < 0.001 with both estimates). Gametocytes were present at day 28 in 13% of the AM group compared with 3% of the ACT group (P = 0.005).…”
Section: Clinical Efficacymentioning
confidence: 87%
“…11 A prospective dose escalating clinical trial of Argemone mexicana decoction (AM) following a local recipe, in patients with uncomplicated malaria, found a dose-response correlation and a good safety profile. 16 In addition to its promising profile, we observed that AM was often readily available where and when modern drugs of acceptable quality were not. 11 The purpose of this study was to compare two strategies for the home-based management of presumed uncomplicated malaria: AM as first line with ACT as second line, versus ACT as first line.…”
Section: Introductionmentioning
confidence: 95%
“…Although we provided all patients with the same amount of plant material and gave the same instructions on the preparation of the decoction, we were not able to ensure that the preparation and dosage of the decoction was identical between patients and between episodes for the same patient. In a previous study we did provide a standard decoction (prepared by the traditional healer) to all patients 6 but we felt that this would not be a practical public health intervention. In the present study we improved the practicality of the intervention at the expense of a level of standardisation.…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 99%
“…After completion of toxicological studies, a dose-escalating clinical study showed a dose response, no serious adverse events and a sharp decline in parasitaemia (from a geometric mean of 14 859 at day 0 to a geometric mean of 174 parasites per mcl at day 4) although generally without total parasite clearance. 6 Two strategies for HMM were compared in a randomised controlled trial (RCT): AM as first line treatment with artesunate/amodiaquine (As/Aq) as second line ('AM group'); or the standard As/Aq as first line with another artemisinin combination therapy (ACT), arthemeter/lumefantrine, as second line ('ACT group'). 7 Following the usual practice of assessing antimalarial treatments by outcome in the 28 days after diagnosis, we found that progress to severe malaria was 1.9% in children aged ≤5 years in both groups, and 0% among those aged >5years old, so that the incidence of severe malaria was kept to a lower level than reported in comparable studies of HMM.…”
Section: Introductionmentioning
confidence: 99%
“…6 We conducted systematic reviews of eight widely used African traditional plant medicines, and identified only one (Pelargonium sidoides), which has been extensively studied in human trials albeit none of these on the African continent. 7 We identified three published trials of plants conducted in Mali 8,9 and Nigeria, 10 a report of two unpublished trials, 11 and one unconfirmed trial. Encouragingly, two plant products (P. sidoides and Niprisan) have been evaluated in Cochrane systematic reviews.…”
mentioning
confidence: 99%